(05.02)
A system of equations is shown below:
x + 3y = 5 (equation 1)
7x - 8y = 6 (equation 2)
A student wants to prove that if equation 2 is kept unchanged and equation 1 is
replaced with the sum of equation 1 and a multiple of equation 2, the solution to the
new system of equations is the same as the solution to the original system of
equations. If equation 2 is multiplied by 1, which of the following steps should the
student use for the proof? (4 points)

Respuesta :

The student would use the following step for the proof

Show that the solutions to [tex]7x - 8y = 6[/tex] and [tex]8x - 5y = 11[/tex] is the same as the solution of the original system

The system of equations is given as:

[tex]x + 3y = 5[/tex]

[tex]7x - 8y = 6[/tex]

Add both equations

[tex]x + 7x + 3y- 8y = 5 + 6[/tex]

[tex]8x - 5y = 11[/tex]

So, the new system of equations would be:

[tex]7x - 8y = 6[/tex]

[tex]8x - 5y = 11[/tex]

To prove that both equations would have the same solution, the student has to solve for x and y in both systems

Read more about systems of equations at:

https://brainly.com/question/14323743